2016
DOI: 10.1104/pp.16.01099
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor ATHB5 Affects GA-Mediated Plasticity in Hypocotyl Cell Growth during Seed Germination

Abstract: Gibberellic acid (GA)-mediated cell expansion initiates the seed-to-seedling transition in plants and is repressed by DELLA proteins. Using digital single-cell analysis, we identified a cellular subdomain within the midhypocotyl, whose expansion drives the final step of this developmental transition under optimal conditions. Using network inference, the transcription factor ATHB5 was identified as a genetic factor whose localized expression promotes GA-mediated expansion specifically within these cells. Both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 60 publications
(88 reference statements)
1
39
0
Order By: Relevance
“…The lines used in this study are listed in SI Appendix, Supplementary Table 1. GUS activity was quantified using the fluorometric assays described by Stamm et al (46).…”
Section: Methodsmentioning
confidence: 99%
“…The lines used in this study are listed in SI Appendix, Supplementary Table 1. GUS activity was quantified using the fluorometric assays described by Stamm et al (46).…”
Section: Methodsmentioning
confidence: 99%
“…Cell expansion and division also occur under tight spatial regulation (Dekkers et al , ; Zhang et al , ; Topham et al , ; Narsai et al , ; Narsai et al , ). These processes require that specific genes are expressed in specific subsets of cells, under the control of distinct genome regulatory programs (Stamm et al , ; Topham et al , ). Transcription factors have an important role in regulating gene expression spatially and temporally during germination (Bassel et al , ; Narsai et al , ; Sánchez‐Montesino et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of mechanical force adjustments by expansion of endosperm cells surrounding the elongating embryo prior to radicle emergence as critical for successful germination has been identified in Arabidopsis thaliana (Bassel et al, 2014;Sá nchez-Montesino et al, 2018;Stamm et al, 2017). Using cell surface area measurements by confocal imaging and 3D geometry reconstruction, Sá nchez-Montesino et al (2018) identified that the region of the endosperm surrounding the lower hypocotyl and the radicle exhibit the highest expansion rates in imbibed seeds.…”
Section: Biophysical Forces Associated With Seed Germination Are Regumentioning
confidence: 99%